Results of radical surgeries at the complicated colorectal cancer - S. N. Shaeva (Кубанский научный медицинский вестник, 2014)
Surgical treatment is carried out 1998 patients with urgently complications of a cancer of a thick gut which during the period from 2001 to 2011 were treated in hospitals of Smolensk and the Smolensk region. Intestinal obstruction was observed in 1644 cases (82,3%), perforation of a tumor 208 (10,4%), bleeding of 146 (7,3%) (n = 146). From among all operated patients radical operations are executed at patients 1427 (71,4%). Radical surgery was carried out by the patient of advanced and senile age less than at persons of younger age. At men with the complicated cancer of a thick gut the bigger percent of radical operations in comparison with women is noted. Besides, the volume, and nature of operation depended on hospitalization terms from the moment of development of complication, weight of the general state, prevalence of malignant process and existence of the remote metastases.